Factors Influencing the Digital Literacy Competency of College Students in the Industrial Revolution Era 4.0 - Rosalina, Dhian; Yuliari, Kartika; Setianingsih, Dias; Zati, Muhammad Rizqi (Program Pascasarjana, Universitas Riau, 2021)
This study aims to identify the factors that influence digital literacy competence in students in the era of industrial revolution 4.0. This research found that at the Faculty of Economics, the University of Kadiri, the sampling technique used was purposive sampling, and the number of respondents was one hundred students. The analysis used Confirmatory Factor Analysis, the results of the study show that three factors that influence the level of digital literacy competence of students, including 1) Environmental support factors consisting of the campus environment and family roles, 2) Socio-economic conditions factors which include individual financial conditions and criticality of the media, and 3) The intensity factor of media use which includes the use of digital media in daily activities and completion of academic tasks